Energy distribution criteria for drawbell blasting in block caving based on post-blast scanning and back-analysis - Henríquez, JP; Torres, C; Alvarado, C; Morales, D (Caving 2026: Sixth International Conference on Block and Sublevel Caving, 2026)
Drawbell blasting is a critical activity in block caving operations as it directly controls excavation geometry, fragmentation, and cave initiation conditions. Defining suitable explosive energy distribution criteria is challenging due to variable confinement, drilling deviations, and differences between designed and actual explosive charging and blasting by phases. This paper presents a methodology to determine energy distribution criteria for drawbell blasting using a back-analysis approach that integrates post-blast scanning, measured drilling deviation data, and real explosive charging information. The methodology compares the actual excavated geometry obtained from post-blast scanners with numerical simulations of explosive energy distribution generated using real drilling and charging data. By correlating simulated energy contours with scanned drawbell geometries, an energy threshold is identified that best represents the excavation limits achieved in practice. This approach allows the definition of phasedependent energy criteria for phased drawbell blasting. Application of the methodology per phases shows that a Phase 1 blasting (slot or initial centre), characterised by high confinement and limited free face, requires an average explosive energy close to 4.3 MJ/t to ensure adequate rock fracturing and material movement. In contrast, Phases 2 or 3, which benefit from increased free faces and reduced confinement, require significantly lower energy levels, around 2.26 MJ/t. The results highlight the strong influence of confinement conditions on energy demand and demonstrate that energy-based blast design criteria, supported by real post-blast data, can improve blast predictability, excavation quality, and operational safety in block caving drawbell construction.
Keywords: block caving; drawbell blasting; energy distribution; post-blast analysis